Characterization of Humoral Response after COVID-19 Infection in an Unvaccinated Cohort - Martínez-Serrano, Maria; Tormo-Palop, Nuria; Navalpotro-Rodríguez, David; Moreno-Córdoba, Marta; Olmos-Arenas, Roberto; Gimeno-Cardona, Concepción (Archives of Clinical and Biomedical Research, 2021)
Coronavirus disease 2019 (COVID-19), caused by a novel Sarbecovirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread worldwide since December 2019. In our region, cases were initially reported in March 2020. Nine months after COVID-19 infection, we evaluated the serostatus of a cohort of 77 patients. Anti-spike IgG (Euroimmun), both qualitative and quantitative tests, anti-nucleocapsid IgG and anti-spike IgM (Abbott), total nucleocapsid antibodies (Roche), and neutralizing antibodies (DIA.PRO) were analyzed. Anti-spike IgG was detectable in 74% of the subjects and anti-nucleocapsid IgG in 45.5%. The total anti-nucleocapsid antibodies assay was positive for all individuals. Noticeably, the percentage of subjects with detectable IgG(S) and IgG(N) was significantly higher in the age-group over 60 years than in the <60 years group (82% and 60% vs. 59.3% and 18.5%). Median quantitative IgG(S) values were also statistically different: 34.4 RU/mL for the elder group vs 9.5 RU/mL for the younger. We found 76.6% of subjects to be seropositive for neutralizing antibodies. A strong correlation was found between IgG(S) and neutralization assays. These data demonstrate that long-lasting and neutralizing humoral response can be detected in SARS-CoV-2 recovered patients as long as 9 months after infection. Quantitative assays are useful tools in order to measure and compare humoral responses. Now that vaccination programmes are largely stablished all over the country, humoral response after natural infection in naïve population could hardly be studied again in the future.